PERANAN PROTEKTIF DAN NON-PROTECTIF NITRIC OXIDEs(NOs) PADA RESPON IMUN - Budiman, Basuki (PERSATUAN AHLI GIZI INDONESIA, 2008)
THE ROLE OF PROTECTIVE AND NON-PROTECTIVE NITRIC OXIDES (NOs) IN IMMUNE RESPONSNitric oxides (NO), included in this term are radical NO., (ionic) NO-, NO, NO2, NO2-, NO3-, N2O3,N2O4, S-nitrosothiols, peroxynitrite (ONOO-), and nitrisyl-metal complex. NOs are radical substances which have characteristic both protective and non-protective immunity due to unable to distinguish pathogen DNA or host DNA. NO is by_product of arginine metabolism. NO plays roles in muscle relaxation to prevent platelets aggregation, as intra cell neurotransmitter, mediated macrophage of tumor cell and bacteria. The activity is under controlled by NO-synthetase (NOS) which has three isomers, namely NOS1 or neural NOS (nNOS), NOS2 or inducible NOS (iNOS) and NOS3 or endothelial NOS (eNOS). The role of iNOS/NO in immune system could be as a protective and non-protective which work simultaneously and depend on the immune system equilibrium. The function of iNOS/NO is as regulator and effector. As regulator the function includes change of lymphocyte from proliferation and modulated cytokine response. As effector the function includes necrosis and immnunoprotective activities. The main target of NO 2 toxicity is lungs but depends on the concentration of toxicity and duration of exposure to the targetKeywords: arginine, immonology, NOS, nitric oxide, protective